Asthma and Emotional Factor - Jusuf Rukman; I. Boediman; NastIti N. Rahayu (Paediatrica Indonesiana, 1983)
The case of boy of 12 years old suffering from recurrent asthmatic attacks has been reported. Treatment with several antiasthmatic drugs and acupuncture did not prevent recurrency. Psychiatric examination revealed an immature personality and anxiety state. Combined management consisting of medicaments, psychotherapy and parental counceling gave complete improvement.